Characteristics of body mass index and sodium intake of adults with hypertension family history in Yogyakarta - Setyawati, Ika (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2023)
Hypertension is a progression of prehypertension due to the accumulation of several non-genetic risk factors (environmental factors) that occur together (common underlying risk factors) or genetic factors or the interaction between the two. Risk factors for hypertension that can be controlled include high sodium intake, lack of physical activity, obesity, smoking, and alcohol consumption, while risk factors that cannot be controlled include increasing age, gender, and a family or genetic history of hypertension. This study aimed to determine the characteristics of Body Mass Index (BMI) and sodium intake in adults with a family history of hypertension in Yogyakarta. This study used a case-control design. Subjects studied were healthy individuals with a family history of hypertension as case subjects (n = 42), and control subjects were individuals without a family history of hypertension (n = 41). Body mass index (BMI) was measured with anthropometry, and sodium intake was measured using a quantitative food frequency questionnaire. Independent Sample T-test and Chi-Square test analyzed the data with a significance level of p < 0.05. The average BMI and sodium intake are higher in the case group than in the control group. There was no significant association between BMI and sodium intake and risk factors of hypertension (p>0.05). Body mass index and sodium intake in the case and control group were not significant differences (p>0.05). The BMI values and sodium intake levels were higher in the group of individuals with a family history of hypertension compared to those without a family history of hypertension, but not statistically significant.